Determination of the optimum conditions for de-icing salt scaling resistance of concrete by visual examination and surface scaling - Tasdemir, Mehmet Ali; Gul, Rüstem; Şahi̇n, Remzi; Çeli̇k, Cafer (Elsevier BV, 2010)
Abstract One of the main objectives of this work is to determine the most important parameter that affects the scaling resistance of concrete. Another objective is to investigate combined effects of finishing treatment and air-entrainment on the freeze–thaw scaling of horizontal concrete surfaces subjected to de-icing salt exposure. The parameters studied in this work were; water–cement ratio, cement content, curing condition, the air-entraining admixture, and second finishing treatment. The total number of freeze–thaw cycles was 50. In the experiments, both visual examination according to ASTM C 672 and scaling test methods were considered. The parameters studied were optimized using Taguchi Optimisation Method. It has been shown that the use of de-icing salt on concrete surface causes gradual deterioration from the surface into the inner section. There is a significant positive effect of air-entrainment on the freeze–thaw scaling at horizontal concrete surfaces. It can be concluded that the second finishing treatment has a positive effect on first cycles but loses its effect on the proceeding cycles.